PENGARUH ROTASI PEGAWAI TERHADAP KEBIJAKAN PENGELOLAAN JURNAL ILMIAH PASCA DIBERLAKUKANNYA AKREDITASI BERKALA ILMIAH ELEKTRONIK - Ardiansyah, Erlan Aditya; Nur, Mohamad Ichsana (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2020)
The study aimed to describe job rotation influence on scientific journal management policy after the implementation of national electronic journal accreditation. Job rotation in Universitas Padjadjaran (Unpad) was regulated in order to conduct career mapping within the process of permanent employee recruitment. Journal management unit of Faculty of Medicine Unpad managing scientific journal including International Journal of Integrated Health Sciences (IJIHS) was affected by job rotation policy. The method used in this study was qualitative method. The data collected were administrative archives such as assignment letters of the editorial board, documents, and file in IJIHS. The results showed that job rotation can become a problem for journal management. Lack of human resource causes problems in scientific publication, particularly magazine distribution. Job rotation can cause problems for journal management. Keywords: Job Rotation, journal editorial, national journal accreditation